Morphological description and phylogenetic characterization of hydra (Cnidaria: Hydrozoa) from São Paulo state, Brazil - Deserti, María I.; Durán-Fuentes, Jeferson A. [UNESP]; Maronna, Maximiliano M. [UNESP]; Morandini, André C.; Acuña, Fabián H.; Stampar, Sergio N. [UNESP] (Elsevier, 2025)
The genus Hydra (Cnidaria, Hydrozoa) comprises a group of aquatic organisms that inhabit freshwater bodies worldwide, except for Antarctica. Hydras are widely recognized for their significant regenerative capacity and simple body plan. Despite the importance of these organisms in freshwater environments and due to the abundance and diversity of freshwater bodies in the Brazilian territory, curiously, this genus and other freshwater cnidarians are understudied. To assess the diversity of hydra in Brazil, we collected specimens from eight freshwater bodies in the SE and S of the country and built a phylogeny using a COI marker and comparing the morphologies with endemic species. These analyzes have yielded encouraging results, mainly the discovery of the species Hydra sinensis originating in China, highlighting the need to expand studies in less explored areas to better understand the relationship between species represented in Brazil and those from other regions of the world. Molecular and phylogenetic inferences, as proxies for species identity are essential to advance our knowledge of the diversity and evolution of Hydra and its relationship with different freshwater ecosystems in Brazil.
Keywords: Brazil; Cnidaria; Freshwater; Hydra